Dual infection of maxillary sinus masquerading as a malignant lesion; A rare presentation (Journal of Pathology of Nepal, 2024)
Primary sinonasal tuberculosis is a rare form of TB even in developing countries where TB is prevalent and invasive mycotic infection is more common in immunocompromised patients. It is unusual to have a dual infection with tuberculosis and mycosis in the maxillary region mimicking a neoplastic process and causing bone erosion. A 49-year old male presented with 2-year history of left-sided facial swelling. On microscopic examination, epithelioid cell granulomas, chronic inflammatory infiltrate, macrophages, giant cells, and focal necrosis were seen. Ziehl Neelsen staining for acid-fast bacilli with 20% H2SO4 was positive. Fungal hyphae were also seen in the sections examined. Special stains (Periodic acid-Schiff and Grocott’s methenamine silver stain) for fungal hyphae were positive. Mycosis and tuberculosis should always be considered in the differential diagnosis of maxillary lesions or sinusitis.